Students Responses Towards Google Classroom As A Digital Learning Platform In Target-Based Learning: (A Qualitative Descriptive Study) - M. Meilan Diamond Krisna; Iin Baroroh Ma’arif; Yuyun Bahtiar; Luluk Choirun Nisak Nur (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research examines students' responses toward Google Classroom as a digital learning platform in target-based English learning at Kresna English Course, Kampung Inggris, Pare, Kediri. The study aimed to identify students' perceptions of Google Classroom's usability and accessibility, and analyze their experiences using the platform's features for English learning tasks. Employing a qualitative descriptive approach, data was collected through observations, interviews, and documentation from 15 respondents who participated in online English courses. The findings revealed that most students perceived Google Classroom positively for its flexibility, organization of materials, and accessibility. However, challenges were identified including technical obstacles (unstable internet connections, device limitations), lack of collaboration features, and initial difficulties in navigating the platform. The research concluded that while Google Classroom has significant potential to support target-based learning in English courses, its effectiveness depends heavily on technological infrastructure readiness, digital literacy of users, and implementation strategies. The study recommends developing better technological infrastructure, providing comprehensive training for users, creating more interactive content, implementing thorough feedback systems, and integrating collaborative features to maximize the platform's benefits in English language education.